VHDL : programming by example. - Perry, Douglas L., ....- (New York : McGraw-Hill, 2002)
Chapter 1: Introduction to VHDL Chapter 2: Behavioral Modeling Chapter 3: Sequential Processing Chapter 4: Data Types Chapter 5: Subprograms and Packages Chapter 6: Predefined Attributes Chapter 7: Configurations Chapter 8: Advanced Topics Chapter 9: Synthesis Chapter 10: VHDL Systems Chapter 11: High Level Design Flow Chapter 12: Top-Level System Design Chapter 13: CPU: Synthesis Description Chapter 14: CPU: RTL Simulation Chapter 15: CPU Design: Synthesis Results Chapter 16: Place and Route Chapter 17: CPU: VITAL Simulation Chapter 18: At Speed Debugging Techniques Appendix A: Standard Logic Package Appendix B: VHDL Reference Tables Appendix C: Reading VHDL BNF Appendix D: VHDL93 Updates
Keywords: VHDL (vhsic hardware description language).